Los actores de la vida universitaria en la España de los siglos xix y xx - Jean–Louis Guereña (Cahiers de Civilisation Espagnole Contemporaine)
The academic history, traditionally performed by lawyers, is in Spain a growing research field, with constantly renewed methodological approaches and thematic diversification throughout the last thirty years. As part of a collective research, it has advanced considerably, not only in knowledge -both quantitative and qualitative- of essential actors in academic life -university teachers and students- at various historical moments of contemporary Spain -mainly during the Restoration and under Franco, especially from 1939 to 1956- but also in their interpretation and the way we consider them. In particular, the prosopographical approach is now a relatively common practice among researchers dealing with some attention to history teachers and students. However, the study of university administration is less studied.